The Effect of Project-Based Learning on Speaking Skills: A Quasi-Experimental Study in a Sports-Talent High School - Muhammad Faqih Al Farisi; Ferri Susanto; Anita Anita (Journal of Innovation in Teaching and Instructional Media, 2025)
This study examined the effect of Project-Based Learning (PjBL) on the speaking skills of eleventh-grade students at SMAN Keberbakatan Olahraga Kota Bengkulu. A quasi-experimental design with a quantitative approach was employed. The study was conducted from August to September 2025 and involved an experimental class taught using PjBL and a control class taught using a conventional method. Students’ speaking skills were measured through pre-test and post-test assessments, and data were analyzed using t-tests and F-tests. Results showed that students taught using PjBL experienced an improvement in speaking skills, with mean scores increasing from 21.95 to 36.4. However, the control class showed a greater improvement, with mean scores rising from 28.85 to 68.8. Statistical analysis indicated a significant difference between the two groups, favoring the conventional method. The findings suggest that conventional teaching methods may be more effective in contexts where students are more familiar with direct instruction. This study provides context-based evidence that PjBL is not always more effective than conventional methods in improving speaking skills.